Analysis of labor productivity on the production of parts bs-62632-60m00 at Putra Kemuning Company - Arbaeni Arba (Geuthèë Institute, Aceh, 2023)
In a company, several aspects can increase profit, one of which is productivity. Productivity measurement can improve productivity in the future by taking into account the calculation of all raw material inputs, energy, labor, and capital used in a company to show the productivity of the products produced. In general, the concept of productivity is a comparison between output and input per unit of time. This study uses observational data collection techniques to observe production results and the number of workers working every day. This study also uses data collection techniques by interviewing company parties, especially in the production department at PT. Yellow Son. PT. Putra Kemuning is one of the manufacturing companies in Karawang Regency which is engaged in stamping, assy welding, jigs and dies, automotive and non-automotive. Value of labor productivity in the production section against Bracket production results from April to June 2021 at PT. Putra Kemuning is good enough because the calculation results are more than 100% or 1 (one) every month. The partial productivity value of the total workforce for a year is 42.92% with an average value of 14.2%. And all factors are said to be productive and the company still gets profit because there is no productivity value below 1 (one).